Fabrication of Ag and Ni Nanocatalyst with Enhanced Efficiency - Tajamal Hussain; Mira Tul Zubaida Butt; Mirza Nadeem Ahmed; Muhammad Hamid Raza; Zahoor Hussain Farooqi; Khurram Shehzad; Adnan Mujahid; Rabia Batool (Journal of Chemistry)
Metal nanoparticles (NPs) have received significant attention in last decade because of their unique properties. In this work, two different metal NPs have been prepared and their catalytic activities are compared with conventional catalyst. In first case, Ag NPs were synthesized by chemical reduction method in ethanolic medium. Synthesized Ag NPs were characterized by scanning electron microscope (SEM) images which indicated an average particle size of Ag around 250 nm. The catalytic activity of Ag NPs was investigated for the oxidative mineralization of methylene blue dye. Comparative studies suggested that Ag NPs possess enhanced catalytic activity compared to bulk Ag. In second approach, supported Ni NPs were fabricated using Al2O3 as supporting surface; that is, Ni NPs get adsorbed on Al2O3 through in situ reduction reaction. Oxidative degradation of methylene blue indicated that catalytic activity of supported Ni/Al2O3 is about five times higher than simple Ni as catalyst.